The Role of Departmental Secretaries Personal reflections on the breadth of responsibilities today - Podger, Andrew (Australia and New Zealand School of Government (ANZSOG), 2009)
Andrew Podger's monograph, The Role of Departmental Secretaries, Personal reflections on the breadth of responsibilities today, is an important contribution to the broader public policy discourse in Australia. Andrew has been, at times, an unflinching commentator on issues of bureaucratic performance, accountability and responsiveness to government. Andrew's reflections are drawn from his own experiences within the inner circle of Australian policy-making. In this monograph, he presents a highly nuanced portrait of the role of Commonwealth departmental secretaries. Although a 'player' himself at key moments in recent policy history, Andrew is a dispassionate and thoughtful observer of events. This is not merely a memoir: this work is rich in analysis and Andrew offers a number of 'lessons learned' to be heeded (or not) by the present and future generations of policy practitioners.